Strengthening Financial Competence Through Village Financial Report Training For Sub District Heads And Officials In Kuningan Regency - Hamzah, Amir; Wiharno, Herma (Inaba of Community Services Journal, 2025)
This community service activity aims to enhance the abilities of district heads in Kuningan Regency in preparing village financial reports, an essential aspect of budget management and financial transparency. This topic was chosen since many district heads have not fully understood Government Accounting Standards (SAP) and the proper techniques for financial report preparation. The methods used in this activity include interactive training involving presentations, discussions, and hands-on practice, along with evaluations through pretests and post tests. The results indicate a significant increase in participants’ understanding, with average pretest scores rising from 45% to 80% in the posttest. Additionally, feedback from participants shows high satisfaction with the quality of the material and teaching methods. These findings highlight the importance of ongoing training in strengthening the capacity of district heads, contributing to better and more accountable village fiscal management. In conclusion, this training successfully improved district heads’ understanding and skills in preparing village financial reports, which is expected to be implemented in their daily duties.